Understanding Islamic Banking among Street Vendors (Study on The Street Vendors in Kajen Square, Pekalongan Regency) - ADELLA, DESY (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to determine the level of understanding of street vendors in Kajen Square, Pekalongan Regency towards Islamic banks. Islamic banks operate based on Islamic principles that prohibit usury and implement a profit-sharing system, which is theoretically more in line with the beliefs of the majority of Muslims. However, at the level of small business actors such as street vendors, understanding of these concepts still varies. This study used a qualitative approach with an interview method to collect data from a number of street vendors operating in the area. The results showed that the majority of vendors have a limited understanding of Islamic banking, although some showed interest in using Islamic banking services if more information and support were available. This study concludes that there is a need for more intensive education and a more effective socialization approach from Islamic banks to increase the understanding and participation of street vendors in the Islamic banking system.